Application of the phase difference correct method in rolling bearing fault diagnosis. Issue 4 (December 2017) - Li, Xinyi; Xie, Zhijiang; Luo, Jiufei
On the basis of empirical mode decomposition and teager energy operator, the new approach for rolling bearing fault diagnosis based on phase difference correction method is presented. It focuses on improving the identification precision of characteristic defect frequency of rolling bearing. Firstly, fault vibration signal is decomposed into finite number of intrinsic mode functions by empirical mode decomposition method. Secondly, computing the kurtosis value and correlation coefficient between intrinsic mode functions and original signal, then the reasonable intrinsic mode function is selected to demodulate by teager energy operator through the correlation coefficient and kurtosis value. Finally, the accurate characteristic defect frequency can be estimated by using phase difference correction method to correct the demodulation spectrum. The proposed method is applied in actual fault signals of rolling bearing with inner race damage and outer race damage. The results showed that, compared with the method without spectrum correction, the improved method receives better effect to identify characteristic defect frequency.